(untitled) (European Science Methodical Journal, 2024)
The paper evaluates the specificity and diagnostic significance of such widely used diagnostic vestibular tests as finger to nose, finger to finger test, Barr-Fisher test, adiadochokinesis test, balance tests in Romberg pose simple and complicated, straight line walking, flank gait, and Fukuda marching test. The peculiarities of their course in patients with peripheral, central and mixed type of vestibular analyzer lesions are discussed. The optimal tests for determining the level of vestibular analyzer lesion at the initial examination of a patient with vertigo are proposed.